Conference ― CRIOSFERA: POTENCIAL EFFECTS OF COASTAL EROSION AND SEA LEVEL RISE - Gama Campillo, Lilia María (Kuxulkab’, 2025)
Speech alluding to the keynote address "Cryosphere: potential effects of coastal erosion and sea level rise", delivered on October 21, 2025 in commemoration of the "International Year of Glacier Conservation", an event organized by the "Water Resources and Hydraulic Infrastructure Commission" of the Senate of the Congress of the Union, also called the "Senate of the Republic".